Microstructural evolution in MSnO3 ceramics derived via self-heat-sustained (SHS) reaction technique - Azad, Abdul-Majeed; Shyan, Lucia Liew Woan; Pang, Toh Yen; Nee, Chen Hon (Elsevier, 2000)
A thorough study of MSnO3 (M = Ca, Sr and Ba) compounds with respect to their synthesis, processing and microstructural characterization has been made. In order to establish a standard methodology with identical and beneficial microstructure and reproducible electrical characteristics, a novel preparative method called self-heat-sustained (SHS) reaction technique was employed. Evolution of microstructure which is intimately related to the envisaged properties in the ceramics, was closely and systematically followed in terms of wide temperature-soak time (T-t) profiles. The results showed that while a well-densified microstructure with small grain size (approximately 1 μm) and near zero porosity could be obtained by selecting a sintering schedule of 1350 °C/x h (48 h<x≤60 h) for CaSnO3 samples, very well sintered samples with relatively larger grains (3-5 μm) and minimal porosity could also be obtained by sintering at 1600 °C for 2 h. Well-densified microstructure with small grain size and zero or near zero porosity could be obtained by a sintering schedule of 1350 °C/x h (12 h<x≤24 h) in SrSnO3 samples. Sintering of BaSnO3 proved to be the most difficult. The BaSnO3 samples could only be densified to the desired level by soaking the powder compacts for 2 h at 1600 °C. The `sugar cube' features were replaced by the spherical grains (average size 1-2 μm).